A composite rupture model for the great 1950 Assam earthquake across the cusp of the East Himalayan Syntaxis - Coudurier-Curveur, A. (2020)
Although the M=w8.7, 1950 Assam earthquake endures as the largest continental earthquake ever recorded, its exact source and mechanism remain contentious. In this paper, we jointly analyze the spatial distributions of reappraised aftershocks and landslides, and provide new field evidence for its hitherto unknown surface rupture extent along the Mishmi and Abor Hills. Within both mountain fronts, relocated aftershocks and fresh landslide scars spread over an area of ≈330 km by 100 km. The former are more abundant in the Abor Hills while the later mostly affect the front of the Mishmi Hills. We found steep seismic scarps cutting across fluvial deposits and bounding recently uplifted terraces, some of which less than two thousand years or even a couple centuries old, at several sites along both mountain fronts. They likely attest to a minimum 200 km-long 1950 surface rupture on both the Mishmi and Main Himalayan Frontal Thrusts (MT and MFT, respectively), crossing the East Himalayan Syntaxis. At two key sites (Wakro and Pasighat), co-seismic surface throw appears to have been over twice as large on the MT as on the MFT (7.6 ± 0.2 m vs. >2.6 ± 0.1 m), in keeping with the relative, average mountain heights (3200 m vs. 1400 m), mapped landslide scar numbers (182 vs. 96), and average thrust dips (25–28° vs. 13–15°) consistent with relocated aftershocks depths. Corresponding average slip amounts at depth would have been ≈17 and ≈11 m on the MT and MFT, respectively, while surface slip at Wakro might have reached ≈34 m. Note that this amount of superficial slip would be out of reach using classic paleo-seismological trenching to reconstruct paleo-earthquake history. Most of the 1950 first arrivals fit with a composite focal mechanism co-involving the two shallow-dipping thrust planes. Their intersection lies roughly beneath the Dibang Valley, implying forced slip parallel to GPS vectors across the East Himalayan Syntaxis. Successive, near-identical, terrace uplifts at Wakro suggest near-characteristic slip during the last two surface rupturing earthquakes, while terrace boulder ages may be taken to imply bi-millennial return time for 1950-size events. As in Nepal, East-Himalayan mega-quakes are not blind and release most of the elastic, interseismic shortening that accumulates across the range.